Analisis Penerapan Kurikulum Merdeka Belajar pada Mata Pelajaran Bahasa Indonesia di SMPN 1 Puri Mojokerto - Mardliyah, Asih Andriyati (Jurnal Simki Postgraduate, 2023)
The purpose of this research is to describe the planning and implementation of learning Indonesian in the implementation of the independent learning curriculum at SMP N 1 Puri. This research is a qualitative research with a field study approach. Data collection techniques through observation, interviews, and documentation. The data analysis technique used is Miles and Huberman's interactive analysis technique, namely 1) data collection, 2) data reduction, 3) data verification, and 4) display. The results of this study are that the teacher has carried out learning according to the independent learning curriculum, namely both in terms of planning and implementing the independent learning curriculum in class. The teacher carries out learning with process differentiation and content differentiation methods. In addition, teachers have also used project-based learning methods. The difference between the independent learning curriculum and the previous curriculum is the existence of project-based learning which encourages students to work together with colleagues so that students' critical thinking skills increase.